Analisis Hukum Terhadap Perlindungan Pengangkatan Anak di Kabupaten Luwu Utara - Sinilele, Ashar (Al-Daulah : Journal of Criminal Law and State Administration Law, 2016)
This article  can  give  you an idea that the  adoption of children in northern   Luwu   not   in   accordance   with   applicable   laws   and regulations so as not to provide legal certainty for adopted children in the future. In addition, the need to reform the law on the adoption of children so that the adoptive parents are not arbitrary to foster children. Legal protection for adopted children in Luwu Utara has not run as expected because the number of adopted children are neglected.